Enhance Transparency Accounting Information As a Sipp Application And Case Financial Application In Presenting The Financial Statements of Case in The Environment of Religious Jurisdictions - Theresia Atika Sari Br. Ginting; Rahima Br Purba; Puja Rizqy Ramadhan (Britain International for Academic Research (BIAR) Publisher, 2022)
Today, along with the times, we are required to be able to adapt to the rapid development of information technology, where every activity or job is made easier by the emergence of various digital-based systems or applications that uphold the principles of effectiveness, and efficiency and modernity. So that now various agencies both from government, private sector, and others continue to innovate in the use of technology to facilitate work while still paying attention to the accuracy of results and ease of work supervision, this aims to improve the quality of employee performance and achieve the agency's goals. Initially, the implementation of case financial administration activities within the Religious Courts was still carried out manually. By the cashier as a duty supervisor, each financial transaction is recorded in the Root Financial Master Book according to the registered case number. The recording of each transaction is carried out on a cash basis. The cashier will record the income from the down-payment of incoming cases and incur costs related to the case process such as processing fees, non-tax state income (PNBP), notification of summons to the Plaintiff/Applicant/Defendant/Respondent, notification of notification, local inspection (decent), editorial staff stamp duty and others, or make a return of the remaining down payment to the parties whose case has been decided in the trial. Considering that the recording activities are related to the registration of incoming cases, trial activities, the existence of cases that have been dropped as well as daily transactions that are handed over to each Treasurer and Bailiff. Likewise, when presenting case financial reports, journaling is done manually which is of course quite time-consuming and prone to recording errors. As the Case, Tracking Information System (SIPP) application, which is further complemented by the Badilag Case Financial Application, enables the management of case financial administration and reporting to be carried out effectively, efficiently, and transparently. The way it works is by inputting every case financial transaction into the SIPP, the data is directly integrated with the e-Financial application